Pengaruh Penggunaan Media Animasi Berbasis Multimedia terhadap Minat Belajar Siswa pada Mata Pelajaran Pendidikan Agama dan Budi Pekerti - Voni Miranda; Sulaiman Sulaiman (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
In PAI learning the learning process is still often done conventionally and the learning media used are less varied which results in student interest in PAI learning is still low. The purposes of this study are: 1. To find out how the use of multimedia-based animation media in PAI subjects at SMK Negeri 2 Padang. 2. To find out students' interest in learning by using multimedia-based animation media in PAI learning. 3. To determine the effect of multimedia-based animation media on PAI subjects. This study uses a pre-experimental method with a one-shot case study design. The sample in this study was class XI TKJ 1 and 2 at SMK N 2 Padang. Data was collected through a questionnaire and the analysis used was simple linear regression. From the analysis proves that animation media has an effect on students' interest in learning, as evidenced by the data generated in class XI TKJ 1 on average all students pay attention and focus during learning only a few people do not focus or follow the lesson well. Likewise with class XI TKJ 2 the number of students who did not take part in learning was 4 people. Based on the results of the f test, the results of the f table > f count are 9.543 > 4.00 with a sign value of 0.003 <0.05, which means that the X variable has an influence on the Y variable and H1 is accepted. And the results of the t test are found that the results of t count> t table 3.089> 2.00100, which means that H1 is accepted and H0 is rejected. It is hoped that teachers will be more active in teaching and learning activities and teachers are expected to be able to make other learning media to make it easier for students to understand learning with the help of media including animation media.